Implementasi Pengambilan Keputusan Taktis Melalui Analisis Biaya Relevan Untuk Meningkatkan Pendapatan (Studi Kasus: Pabrik Rumahan Roti Hangat Keliling di Kota Jambi) - Ayu Feranika; Dwie Ananda Destari; Erin Fatrisia; Delfina Salsabila; Diza Yunia; Naya Aulia Putri; Bayu Setiawan (CV. Ulil Albab Corp, 2024)
The Mobile Warm Bread Home Factory is a Micro, Small and Medium Enterprise (MSME) that processes raw materials into finished products, namely warm bread. The factory produces 2,100 loaves of bread a day, with flavor variants such as chocolate, strawberry, coconut, green bean, srikaya, and messes. In the production process, the mobile hot bread home factory still uses gas oven production tools or machines, in the midst of the development of equipment or Machines that use electrical energy are electric ovens. The aim of this research is to analyze the application of relevant costs in decision making to continue or replace a gas oven with an electric oven. This research methodology uses descriptive qualitative, with data collection through in-depth interviews, observation and data analysis. Decision making will always be related to the future so business owners need to review these decisions. To help business owners make the right decisions, by choosing the best decision alternative among the available decision alternatives. The results of this analysis show that the most appropriate decision is to continue using a gas oven because it obtains the most relevant total results and benefits rather than replacing it with an electric oven.